Estimation of flood damage intensity based on global damage-depth functions in Jajroud river area - Amir Mohammad Hooshmand; Seyed Abbas Hosseini; Bagher Ghermezcheshmeh (مهندسی منابع آب, 2023)
AbstractIntroduction: One of the solutions for flood management is flood zoning in different return periods, which can be an essential tool in determining development strategies and reducing flood damage. Calculating flood damage in existing uses provides useful information for various organizations such as insurance to be aware of the amount of damage in different uses in the event of a flood.Methods: The study area is located in Rudak basin. In this regard, first maps, required hydrological data and DEM of the study area were prepared. Then, according to the flow data, the maximum annual moments in Rudak hydrometric station were fitted with normal log distribution (as the best distribution) and the flow rate was obtained in four return periods. Then, a single hydrograph was obtained by SCS method for different return periods. Then, using the HEC-RAS2D model, the flood zone with the mentioned return period is obtained and finally, based on the global damage-depth functions, the amount of damage in the return period is based on different uses, including residential, commercial, agricultural, roads was calculated.Findings: By comparing the results of flood zoning and damage maps, which with increasing flood return period, the amount of damage and the area of ​​high-risk zone increases. The amount of flood zone in the return periods of 5, 25, 50 and 100 years is equal to 17.9, 18.9, 19.4, 19.9 hectares, respectively. Most of the damage is related to agricultural lands and then lands with commercial use. The rate of increase in damage to the area between floods 5 and 25 return period is about 47%, between floods 25 and 50 return period is about 6%, and between floods 50 and 100 years is about 15%. Therefore, a 50-year flood can be proposed to determine the flood protection plans of the region.